Anti-microbial Activity of Rubus idaeus L. Leaf Extracts in Combination with Antibiotics against Bacterial Triggers of Selected Autoimmune Diseases - Zhang, Chen; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Rubus idaeus L. leaves have been used in traditional healing systems for the treatment of morning sickness, easing labour pains and for preventing miscarriage. Whilst few studies have examined the leaves of this species for therapeutic properties, the fruit have antibacterial activity against multiple bacterial pathogens. This study examines the growth inhibitory effects of R. idaeus leaf extracts, both alone and in combination with conventional antibiotics against bacterial triggers of selected autoimmune inflammatory diseases. Results: Rubus idaeus leaf extracts displayed noteworthy antibacterial activity against several bacterial triggers of autoimmune diseases. The methanolic, aqueous and ethyl acetate extracts were particularly good inhibitors of P. mirabilis, A. baylyi and P. aeruginosa growth, with MIC values as low as 53 µg/mL. Combining the extracts with conventional antibiotics potentiated the inhibitory activity for several combinations containing chloramphenicol or gentamicin against A. baylyi. Interestingly, the other combinations were generally non-interactive and no antagonistic interactions were detected, indicating that all combinations can be used without decreasing the efficacy of the therapy. None of the individual components (or the combinations) were toxic in the ALA assay. Conclusion: Rubus idaeus leaf extracts have potential for the prevention and treatment of rheumatoid arthritis and multiple sclerosis when used alone. Furthermore, some combinations of the extracts and conventional antibiotics had greater potency against the bacterial triggers of multiple sclerosis, indicating they may be beneficial for prophylactic therapy in individuals genetically predisposed to that disease.
Keywords: Medicinal plants; Synergy; Rheumatoid arthritis; Ankylosing spondylitis; Multiple sclerosis; Drug combinations; Efflux pump inhibitor